Improved Anti‐Emetic Efficacy of 5‐HT3 Receptor Antagonists in Cancer Patients with Genetic Polymorphisms of ABCB1 (MDR1) Drug Transporter. (6th November 2014) - Zoto, Teuta; Kilickap, Saadettin; Yasar, Umit; Celik, Ismail; Bozkurt, Atilla; Babaoglu, Melih Onder
Abstract Chemotherapy‐induced nausea and vomiting (CINV) remains a major adverse effect decreasing quality of life in patients with cancer. Genetic variations among patients may be responsible for part of the lack of efficacy of anti‐emetic drugs. The aim of this study was to investigate how the genetic variants of the drug transporter ABCB1 (MDR1) gene affect anti‐emetic treatment with 5‐HT3 receptor antagonists. Patients (n = 239) receiving moderately or highly emetogenic chemotherapy and ondansetron or granisetron were included in the study. Anti‐emetic responses were recorded daily. The primary end‐point of the assessment was the total control rates of CINV in the acute and delayed phases after chemotherapy. Genotyping was performed by PCR‐RFLP. In the acute phase, patients with ABCB13435TT, 1236TT or 2677TT genotypes had a higher control rate of CINV than other genotype groups: (64.7% in 3435TT versus 45.7% in 3435CC+CT, p = 0.016; 65.1% in 1236TT versus 46.4% in 1236CC+CT, p = 0.027; 66.7% in 2677TT versus 46.5% in other genotypes, p = 0.021). Subjects carrying homozygous variant alleles together (TT‐TT‐TT) showed a significantly higher protection from nausea and vomiting (67.7% in TT‐TT‐TT versus 47.1% in other genotypes, p = 0.032). After the logistic regression analysis with adjustment for other known covariates, the total control rate was significantly higher in the 3435TT genotype group during the acute phase (p = 0.021). No significant change was found between the total control rates among genotypes in the delayed phase. Each of three 3435TT, C1236TT, 2677TT genotypes of ABCB1 and their combination was associated with about 50% higher anti‐emetic response to 5‐HT3 receptor antagonists in the acute phase of chemotherapy in patients with cancer receiving moderately or highly emetogenic chemotherapy. ABCB1 (MDR1) genotypes may contribute to predict the anti‐emetic efficacy of 5‐HT3 antagonists.